KEANEKARAGAMAN JENIS BURUNG DI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG, SULAWESI SELATAN - Abdul Haris Mustari; Aditya Wahyu Tri Asmoro; Gita Oktarina Eka Pi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2012)
Bantimurung Bulusaraung National Park is an important protected area in Sulawesi. This area has a high ornithological value because it holds many Sulawesi’s endemic species. Bird surveys using MacKinnon species lists and point count were conducted in three types of habitat in Bantimurung and Balocci from 23 February to 7 March 2011 and a total of 57 species were recorded, with the highest number of species found in Balocci Resort. Sixteen species were Sulawesi’s endemic. Keywords: Bantimurung Bulusaraung National Park, birds’ biodiversity